Kualitas hidup manula yang menggunakan gigi tiruan lengkap berdasarkan OHIP -14 di Kota Makassar (Quality of life of elderly using complete denture based on OHIP-14 in Makassar) - Muzdalifah Solina Berutu; Moh. Dharmautama (DiscoverSys Inc., 2015)
Complete dentures are not always functioning well in replacing teeth. Mastication, esthetics and phonetic has beenknown to affect the quality of life. This study aims to determine the quality of life of elderly who use the full denture.Descriptive analytic research with cross sectional study design was conducted in Makassar on May-June 2014. Thesample was obtained by stratified random sampling, by conducting interviews based on OHIP-14 questionnaires, doorto door on 162 elderly respondents. The results show that the highest score of the seven dimensions of OHIP-14 is on thedimensions of physical disability, and the lower the score obtained, the better the quality of life. This research obtaineda mean score of 50.58, so it was concluded that the quality of life of the elderly in Makassar which uses the full denturewas categorized as good.